2021
DOI: 10.1186/s40462-021-00249-7
|View full text |Cite
|
Sign up to set email alerts
|

Migration ecology of western gray catbirds

Abstract: Background For many songbirds in North America, we lack movement details about the full annual cycle, notably outside the breeding season. Understanding how populations are linked spatially between breeding and overwintering periods (migratory connectivity) is crucial to songbird conservation and management. We assessed migratory connectivity for 2 breeding populations of Gray Catbirds (Dumetella carolinensis) west of and within the Rocky Mountains by determining migration routes, stopover site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Our tracking data suggested that within‐season movements outside of the breeding season may be common for black‐headed grosbeaks that breed in California, particularly during the molting period, although larger movements near seasonal transitions may more accurately be considered to be protracted migrations than within‐season movements. Support for non‐breeding season movements has been reported for other migratory landbird species (Cormier et al, 2013 ; Mancuso et al, 2021 ; Ruiz‐Gutierrez et al, 2016 ; Stutchbury et al, 2016 ), and flexibility to move to new sites within seasons may be a critical adaptation for tracking uncertain environmental conditions. Both yearling males that showed within‐molting season movements initially settled in habitats that were less green than those settled in by the older adults.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our tracking data suggested that within‐season movements outside of the breeding season may be common for black‐headed grosbeaks that breed in California, particularly during the molting period, although larger movements near seasonal transitions may more accurately be considered to be protracted migrations than within‐season movements. Support for non‐breeding season movements has been reported for other migratory landbird species (Cormier et al, 2013 ; Mancuso et al, 2021 ; Ruiz‐Gutierrez et al, 2016 ; Stutchbury et al, 2016 ), and flexibility to move to new sites within seasons may be a critical adaptation for tracking uncertain environmental conditions. Both yearling males that showed within‐molting season movements initially settled in habitats that were less green than those settled in by the older adults.…”
Section: Discussionmentioning
confidence: 80%
“…Rapid advances in tracking technology have allowed for identification of these connections for a growing list of migratory animal species (McKinnon et al, 2013 ; Ruegg et al, 2014 ; Rushing et al, 2014 ). However, the value of this information for conservation is relatively limited without also identifying key environmental stressors at different points of the life cycle to better understand the consequences of migratory connections for population dynamics (Mancuso et al, 2021 ; Rushing, Ryder, & Marra 2016 ; Saracco & Rubenstein, 2020 ; Wilson et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In BC, California, and Nayarit, birds were also given three colour bands to aid in resighting. One right outer rectrix (R6) was collected for genetic analyses (and corticosterone, Mancuso et al 2021 , pending). One right inner secondary feather (S4–S6) was collected for hydrogen stable isotope analyses, except in California where no secondaries were collected, but instead, two outer rectrices were taken.…”
Section: Methodsmentioning
confidence: 99%
“…Tags were scheduled to take the fix at 16:00 or 17:00 GMT (9:00 or 10:00 PDT) where birds should be awake and active. We tested the same type of GPS tags for another study before deployment at a stationary location in BC and found that accuracy was within a few meters for many points, and 90% of points were within 100 m (Mancuso et al 2021 ). According to the manufacturer, the lowest levels of accuracy (which ought to be removed) are 300 m (Lotek Wireless Inc. 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Thanks to tracking devices such as light level-geolocators (hereafter "geolocators"), GPS loggers or radio transmitter, we gained knowledge about migration behaviour [4], like timing of migration, migration tracks, locations of overwintering areas and the time they spend in each area [i.e. [6][7][8]. All this information contributes to a better understanding of life-history strategies in long-distance migratory bird species [9,10].…”
Section: Introductionmentioning
confidence: 99%